Zakat and the performance of Islamic banks. Empirical evidence - Haron, Razali; Mohamed Barre, Galad; Abdullah Othman, Anwar Hasan (IGI Global, 2021)
The objective of this study is to examine the performance of Islamic banks (IBs) in Malaysia based on zakat (ZOA and ZOE) and ROA and ROE. This is to effectively understand the factors influencing the performance of IBs in Malaysia. The study employs a balanced panel of 15 IBs for the period 2009-2018 using the System-GMM. The study provides justifications why zakat is the appropriate measurement for IBs’ performance. The study concludes that zakat is an appropriate performance measurement to explain the performance of IBs. This is because zakat is able to explain and truly reflects the performance of IBs and as such, IBs should pay more zakat as they generate more profit. Zakat therefore has a role to contribute to Islamic social finance in the context of IBs. Furthermore, IBs have indispensable roles in supporting the economy of a country through their liquidity creation and risk transformation functions.